Elaphuri Davidiani Cornu Improves Depressive-Like Behavior in Mice and Increases Neurotrophic Factor Expression in Mouse Primary Astrocytes via cAMP and ERK-Dependent Pathways - Zhu, Yue; Liu, Mengqiu; Qu, Suchen; Cao, Cheng; Wei, Chongqi; Meng, Xue-er; Lou, Qianyin; Qian, Dawei; Duan, Jin-ao; Ding, Yuhua; Han, Zhengxiang; Zhao, Ming (Frontiers in Pharmacology, 2020)
Elaphuri Davidiani Cornu (EDC), the natural shedding horn of Elaphurus davidiauus Millne-Edwards, is applied for maintaining physical and mental health of people in ancient China. In current research, we evaluated the antidepressant effect of EDC on depression-like animal models and explored the possible mechanisms on mouse primary astrocyte cultures. It was found that the aqueous extracts of EDC significantly improved depression-like behaviors of depression model mice. Meanwhile, the EDC aqueous extract enhanced expressions of neurotrophic factor NGF and BDNF both in tissues of prefrontal cortex and hippocampus of mice. On mice primary astrocyte cultures, the EDC aqueous extracts significantly increased the neurotrophic factor expressions both on transcriptional and protein levels. The EDC aqueous extracts might exhibit these functions by regulating matrix metalloprotein -9 (MMP-9) enzymes of metabolic pathways of NGF and BDNF. The aqueous extracts of EDC might enhance expressions of neurotrophic factors via cAMP- and ERK-dependent pathways, which was further confirmed by treatment of related inhibitors. These results supplied more scientific evidences for supporting the medical utilization of EDC in drug development for treating major depression disorder.